Recent advances on microplastics pollution and removal from wastewater systems: A critical review. (15th August 2023) - Parashar, Neha; Hait, Subrata
Abstract: Microplastics (MPs) (plastic particles <5 mm) are globally acknowledged as a serious emerging micropollutant, which passes through various pathways in natural habitats and eventually ends up in our food chain. In this context, the present study critically reviews recent advances in MPs sampling and detection, occurrence, fate, and removal in wastewater treatment plants (WWTPs) by delineating their characteristics that manifest toxicity in the environment via effluent discharge. While there is currently no standard protocol in place, this work examined and compared the latest approaches adopted for improved sampling, sample processing, and characterization of MPs via fluorescence imaging and certified reference materials for method validation. MPs concentration from different sources in the WWTPs varies considerably ranging between 0.28 and 18285 MPs/L (raw wastewater), 0.004–750 MPs/L (effluent), and 0.00023–10380 MPs/kg (sludge). Assessment of MPs removal efficiency across different treatment stages in various in WWTPs has been performed and elucidated their removal mechanisms. The overall MPs removal efficiency in primary, secondary, and tertiary treatment stages in WWTPs reported to be around 57–99%, 78.1–99.4%, and 90–99.2%, respectively. Moreover, the review covers advanced treatment methods for removing MPs, including membrane bioreactors, coagulation/flocculation, ultrafiltration, rapid sand filtration, ozonation, disc filtration, and reverse osmosis, which have been found to be highly effective (>99%). Membrane bioreactors have been proclaimed to be the most reliable secondary treatment technique for MPs removal. Coagulation (92.2–95.7%) followed by ozonation (99.2%) as a tertiary treatment chain has been demonstrated to be the most efficient in removing MPs from secondary-treated wastewater effluent. Further, the review delineates the effect of different treatment stages on the physical and chemical characteristics of MPs, associated toxicity, and potential impact factors that can influence the MPs removal efficiency in WWTPs. Conclusively, the merits and demerits of advanced treatment techniques to mitigate MPs pollution from the wastewater system, research gaps, and future perspectives have been highlighted. Graphical abstract: Image 1 Highlights: Recent advances on MPs pollution characterization and removal in WWTPs reviewed. Occurrence in WWTPs: 0.28–18285 MP/L (raw wastewater), 0.00023–10380 MP/kg (sludge). MPs removal in WWTPs: 57–99% (primary), 78–99% (secondary), and 90–99% (tertiary). Most efficient MPs removal process: MBR (secondary) and coagulation-ozonation (tertiary). Hydraulic retention time and organic loading considerably affect MPs removal in WWTPs.